Criminal History and Future Offending of Juveniles Convicted of the Possession of Child Pornography. (August 2014) - Aebi, Marcel; Plattner, Belinda; Ernest, Melanie; Kaszynski, Katie; Bessler, Cornelia
Most child pornography is distributed online. It is estimated that 3% to 15% of child pornography consumers are juveniles. The present study analyzed a consecutive sample of 54 male juveniles convicted of the possession of child pornography. Demographic characteristics, criminal history, and subsequent offending were assessed from criminal files and official reports. Juvenile possessors of child pornography were compared to three different groups of juveniles: Juvenile possessors of other illegal pornography ( n = 42), juveniles who committed a sexual contact offense against a child ( n = 64), and juveniles who committed a sexual contact offense against a peer or adult ( n = 104). Juvenile possessors of child pornography were found to have downloaded the illegal material more frequently and over a longer time period than juvenile possessors of other illegal pornography. Furthermore, juvenile possessors of child pornography differed from juveniles who had committed a sexual contact offense in terms of demographics and showed fewer previous and subsequent offending than juveniles who sexually offended against a peer or adult. We conclude that juvenile possessors of child pornography need a specific target intervention focusing on dysfunctional Internet use and sexually deviant arousal.